The Influence of Village Apparatus Capabilities and Village Financial System Implementation on Village Financial Management Accountability with the Internal Control System as a Moderating Variable in Nalo Tantan District, Merangin Regency - Femi Nurul Atipah; Sri Rahayu; Muhammad Gowon (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to determine the influence of the ability of village officials and the implementation of the village financial system on the accountability of village financial management with the internal control system as a moderating variable in Nalo Tantan sub-district, Merangin Regency. The population in this research is village officials in Nalo Tantan sub-district, Merangin regency consisting of from 7 villages. The sample in this study used a saturated sample, namely a sampling technique using the entire population as a research sample consisting of 56 respondents. This research method uses quantitative methods. This research uses primary data obtained from questionnaires distributed to respondents. The results of the research show that the ability of village officials influences the accountability of village financial management and the implementation of the village financial system influences the accountability of village financial management, while the internal control system is unable to moderate the influence of the ability of village officials on the accountability of village financial management and the internal control system is unable to moderate the influence of system implementation. village finances towards accountability in village financial management.